20 years of “analisis politico” (2008)
“Análisis Político” presents to its readers the reports and articles formulated during the Twentieth anniversary of the journal and IEPRI. The first two texts portray the type of articles published in the journal “Análisis Político”, its contexts and methodologies. The last text present reactions to the perception of the political studies and those of violence in Colombia, defending the role carried out by IEPRI and its publications in that field.